Inactivating the beta 2-microglobulin locus in mouse embryonic stem cells by homologous recombination. - Koller, B H (1989)
We have inactivated, by gene targeting, the endogenous beta 2-microglobulin gene in a mouse embryonic stem cell line. A cloned fragment of the beta 2-microglobulin gene with the coding sequence disrupted by the insertion of the neomycin-resistance gene was used to transfect the embryonic stem cells. G418-resistant colonies were selected and then screened using the polymerase chain reaction to identify those in which the incoming DNA had integrated into the embryonic stem cell genome by homologous recombination. Of a total of 234 G418-resistant colonies screened, 2 correctly targeted colonies were identified. Chimeric mice carrying the inactivated beta 2-microglobulin gene have been obtained from both of these targeted embryonic cell lines. Breeding of offspring from such animals will allow investigation of the effects of homozygous loss of beta 2-microglobulin.